2015
DOI: 10.1007/s11837-014-1272-9
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of Al-12Si Alloy Via Pulsed Selective Laser Melting

Abstract: Additive manufacturing (AM) of metallic materials is experiencing a research and commercialization craze in almost all industrial sectors. However, to date, AM has been limited to a small numbers of alloys. With respect to aluminum, two alloys received some attention: Al-12Si and Al-10Si-1Mg. In both cases, fully dense components have been achieved using a continuous-wave selective laser melting system. In this article, a new approach of selective laser melting using a pulsed-laser source as opposed to a conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 30 publications
1
33
0
2
Order By: Relevance
“…Numerous studies shows that various additive manufacturing techniques had been able to successfully manufacture the Al-Si alloy parts but none of them had attempted to deposit Al-Si alloy on as-casted automotive parts. The scope and practical hurdles of practically implementing AM of Al-Si alloy [1][2][3][4][5] has not been studied in detail. The practical challenges involved in the laser additive manufacturing of Al-11.2Si alloy is discussed in the current study using systematic step by step approach from deposition of Al-11.2Si alloy on substrate to deposition on as-casted part.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies shows that various additive manufacturing techniques had been able to successfully manufacture the Al-Si alloy parts but none of them had attempted to deposit Al-Si alloy on as-casted automotive parts. The scope and practical hurdles of practically implementing AM of Al-Si alloy [1][2][3][4][5] has not been studied in detail. The practical challenges involved in the laser additive manufacturing of Al-11.2Si alloy is discussed in the current study using systematic step by step approach from deposition of Al-11.2Si alloy on substrate to deposition on as-casted part.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of peak power on the density for two different particles sizes (Al-12Si S10 and Al-12Si S20) is given in Figure 5, while CT scan images of the SLM-S10 specimen are given in Figure 6. It is concluded that an increase in hardness is observed in comparison with cast alloy and other SLM studies and the morphology of microstructure depends on thermal gradients and large undercooling [32].…”
Section: Metal Matrix Composites and Metallic Alloysmentioning
confidence: 71%
“…This result contradicts the assumption that Al alloys are difficult to process in A.M. due to their low laser absorptivity. On the other hand, under conditions where the melt pool is smaller than the laser beam – that is, at lower laser power or when using a pulsed instead of a continuous laser source − the laser may interact directly with the powder feedstock and the laser absorptivity may also depend on the powder particle size . Indeed, finer powders have a greater specific surface area exposed to the incident laser, thus resulting in enhanced laser‐particles interactions.…”
Section: Am Of Al Alloysmentioning
confidence: 99%
“…Indeed, finer powders have a greater specific surface area exposed to the incident laser, thus resulting in enhanced laser‐particles interactions. Besides, while most of the work on LBM has been carried using a continuous wave laser source, Chou et al have demonstrated the feasibility of using a pulsed‐laser source …”
Section: Am Of Al Alloysmentioning
confidence: 99%